Identification of genetic lesions in the ribosomal protein gene, RPL41 from human nasopharyngeal derived cell lines - Sultana Parvin, Binti Habeebur Rahman (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Nasopharyngeal carcinoma (NPC) is associated with three RP genes, namely RPL27, RPL37a and RPL41 that were significantly downregulated in all cell lines derived from NPC tissues when compared with nonmalignant nasopharyngeal epithelial cell lines. However, there is no report on RPL41 genes in human nasopharyngeal tissue. The objective of this study is to investigate the correlation between NPC and RPL41 gene sequence using nom1al and tumour cell lines derived from nasopharyngeal tissues. Total RNA of cell lines were used as the starting material and were transcribed into cDNA using M-MLV transcriptase. The 227 bp RPL41 gene was successfully amplified by polymerase chain reaction and was subsequently purified and sent for sequencing. The result shows that there is no nucleotide variation been observed in the coding sequences of RPL41 among these cell lines.